Anxiety and depression in times of COVID and the resilience factor - Meza-Peña, Cecilia; Álvarez-Bermúdez, Javier; NODO MÉXICO, GRUPO PSYCOVID (Horizonte Sanitario, 2022)
Objective: To analyze the effects of the pandemic in its phase II in people from different regions of the country, with respect to the possible appearance of anxiety and depression symptoms and how these were related to resilience.Material and methods: Cross-sectional correlational design, 7,439 people from different states of Mexico participated with a mean age of 36.99 (SD=14.00). The questionnaire was constructed by the PSYCOVID research group taking indicators from different instruments that measure the study variables such as anxiety, depression, and resilience. It showed a reliability of α=0.88.Results: The presence of anxiety was found in 11.5% of the sample, 23.4% with indicators of depression; and 96.9% of the sample manifested resilience. There is a significant and negative correlation between resilience with anxiety (r=-0.108, p=0.000) and with depression (r=-0.100, p=0.000). Regarding anxiety, women obtained higher percentages than men (13.3% vs. 7.5%), while in depression, women presented percentages of 25.5% vs. 18.5% in men. In the case of resilience, resilience is higher in men (97.4% vs. 96.6%). By age group, young adults show more depressive, anxiety and resilience symptoms, compared to middle-aged and older adults.Conclusions: These data are discussed in terms of probable care strategies at the community level and by vulnerable groups.Key words: Anxiety; Depression; Resilience; Pandemics